Binge-eating disorder in Brazilian women on a weight-loss program - Borges, Maria Beatriz Ferrari [UNIFESP] (2002)
Objective: To examine binge-eating disorder (BED) and its association with obesity, weight patterns, and psychopathology in a Brazilian sample of female participants of a weight-loss program in Sdo Paulo, Brazil.Research Methods and Procedures: Two hundred and seventeen overweight (body mass index greater than or equal to 25 kg/m(2)) women, ages 15 to 59 years, enrolled in the Weight Watchers Program were recruited for the study at a program branch meeting after completing the Questionnaire on Eating and Weight Patterns-Revised, Beck Depression Inventory, and the Toronto Alexithymia Scale-20. Participants were categorized into four groups: those who met questionnaire criteria for BED, those who met questionnaire criteria for bulimia nervosa (BN), those that reported binge eating but did not meet all the criteria for any eating disorder (BE), and those with no eating disorder symptoms (No ED). Groups were compared on measures of weight, depressive symptoms, and alexithymia.Results: Binge eating was frequently reported by women in this study (BED, 16.1%; BN, 4.6%; BE, 22.6%). BED women had significantly higher body mass index, greater highest weight ever, and more frequent weight cycling than the No ED group. BED women also reported more depressive symptoms than BE and No ED women, and were more alexithymic than the No ED group. BE women presented more frequent weigh cycling and were also more depressed and alexithymic than the No ED group.Discussion: BED is not uncommon in overweight Brazilian women, and similar to North American and European samples, it is associated with overweight and higher levels of psychopathology in this population.